Wirelessly Powered 3D Printed Hierarchical Biohybrid Robots with Multiscale Mechanical Properties. (3rd May 2022) - Tetsuka, Hiroyuki; Pirrami, Lorenzo; Wang, Ting; Demarchi, Danilo; Shin, Su Ryon
Abstract: The integration of flexible and stretchable electronics into biohybrid soft robotics can spur the development of new approaches for fabricating biohybrid soft machines, thus enabling a wide variety of innovative applications. Inspired by flexible and stretchable wireless‐based bioelectronic devices, untethered biohybrid soft robots are developed that can execute swimming motions, which are remotely controllable by the wireless transmission of electrical power into a cell simulator. To this end, wirelessly‐powered, stretchable, and lightweight cell stimulators are designed to be integrated into muscle bodies without impeding the robots' underwater swimming abilities. The cell stimulators function by generating controlled monophasic pulses of up to ≈9 V in biological environments. By differentiating induced pluripotent stem cell‐derived cardiomyocytes directly on the cell stimulators using an accordion‐inspired, three‐dimensional (3D) printing construct, the native myofiber architecture are replicated with comparable robustness and enhanced contractibility. Wirelessly modulated electrical frequencies enables the control of speed and direction of the biohybrid soft robots. A maximum locomotion speed of ≈580 µm s −1 is achieved in robots possessing a large body size by adjusting the pacing frequency. This innovative approach will provide a platform for building untethered and biohybrid systems for various biomedical applications. Abstract : Wirelessly‐powered, biohybrid soft robots that are inspired by stretchable bioelectronic devices and accordion‐like scaffold designs are demonstrated. The integration of wireless cell stimulators into human cardiac‐tissue‐based muscle actuators realizes electrically controlled movement of robots without requiring batteries and wires. The long penetration depth of the stimulation signal and inherent system extensibility may advance the development of biohybrid robotic systems that are controllable in both in vivo and in vitro environments.